2010
DOI: 10.4066/amj.2101.494
|View full text |Cite
|
Sign up to set email alerts
|

Ear, Nose and Throat disorders in paediatric patients at a rural hospital in India

Abstract: BackgroundThere is a lack of data on paediatric otorhinolaryngology from various Indian populations. This study was undertaken to determine the hospital prevalence of ENT disorders in paediatric population and their relationship with sociodemographic factors in a rural tertiary care hospital in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
36
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 10 publications
9
36
2
3
Order By: Relevance
“…Impacted was seen in 18% of the ear disorders. Similar was the case in a study by Yeli 1l and by Kishve et al, 9 although in a study by Nepali et al, the most common ear disorder was Ear Wax which accounted for over 40% of the cases. 10 We had a low prevalence of otmycosis consisting of 5.8% of the ear disordes and 2.9% of overall ENT disorders.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Impacted was seen in 18% of the ear disorders. Similar was the case in a study by Yeli 1l and by Kishve et al, 9 although in a study by Nepali et al, the most common ear disorder was Ear Wax which accounted for over 40% of the cases. 10 We had a low prevalence of otmycosis consisting of 5.8% of the ear disordes and 2.9% of overall ENT disorders.…”
Section: Discussionsupporting
confidence: 65%
“…Yeli showed epistaxis prevalence of 15% 8 while Sanjay et al showed the prevalence to be 16.6%. 9 Among the throat disorders, pharyngitis was found most common followed by tonsillitis. The same was found in a study by Nepali et al whereas the prevalence of tonsillitis was more in a study by Yeli. This study and its results are applicable to the geographical and socioeconomic status around our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…[5] In studies it has been noted that Otitis Media and its sequelae are most common cause of preventable hearing loss in children in developing countries. [6,7] The major burden reported in India & other developing countries by WHO is due to Chronic Suppurative Otitis Media. [8] Name & Address of Corresponding Author Dr. Nitin Tomar Department of ENT and HNS, Muzaffarnagar Medical College, Muzaffarnagar, Uttar Pradesh, India.…”
Section: Introductionmentioning
confidence: 99%
“…However, ENT diseases are serious public health problems with universal distribution affecting all age groups [1,2]. Although, ear, nose and throat diseases are very important because of the type of morbidities, which may lead to impairment of the physiological functions.…”
Section: Introduction: -mentioning
confidence: 99%
“…Globally, Ear infections considered as one of the leading causes of health care visits and its complications represent important causes of preventable hearing loss, especially in developing countries [1]. While around 0.5% of all upper respiratory tract infections are complicated by sinusitis, the incidence in UK of acute sinusitis ranges from 15 to 40 episodes per 1000 patients per year and it is the secondmost common infectious disease seen by general physicians [2]. However, acute throat infections are the most common infectious diseases seen by family physicians and they are responsible for 2% to 4% of all visits [4,5].…”
Section: Introduction: -mentioning
confidence: 99%